(3fMh COGA eJejR dMdbGJ JMajX GdbQBf GdcQje (B:s ((3JgPjH cJGH GdcJGJjH hGdeOGQS GdbQBfjI(B) /s - (3GdefJOi GdESdGej (B( (3GdQjGV (B)s ((3GdQjGV (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3eDSSI UdGM GdSdje ddfTQ hGdJhRjY ,s, 1999)
(3jJfGhd cJGH (B((3fMh COGA eJejR dMdbGJ JMajX GdbQBf GdcQje(B) (3hGdPj bGe HJCdjag GdefJOi GdESdGej GdQjGV, ehVhY (B((3MdbGJ JMajX GdbQBf GdcQje(B) (3GdcJGH jSJYQV CSGSjGJ hGdCOhGJ GddGReI ddfghV HMdbGJ JMajX GdbQBf GdcQje, ef NdGd GdJYQja HebheGJ TNUjI GdeOQS GdYbOjI hGdCNdGbjI hGdSdhcjI hGdLSOjI hGdeXgQjI, hGdebheGJ GdegfjI(B. (3hhVM WQb JOQjS GdbQBf GdcQje aj GdMdbGJ, hCgejI GdeQGLYI hGdChbGJ GdebJQMI ddeQGLYI, hGdCehQ GdeTLYI ddWGdH Ydi GdeQGLYI(B. (3ceG jbOe WQb ebJQMI ddeQGLYI, hJfHjgGJ ddeOQS CKfGA ETQGag Ydi bjGe GdWdGH HGdeQGLYI, hcjajI EOGQI MdbGJ JMajX GdbQBf GdcQje, ef NdGd JhLjgGJ YGeI dEOGQJgG hdEOGQI GdeOQS dWdGHg, hcjajI Jbhje bQAGI GdWdGH ddbQBf GdcQje hGSJjYGHge ddYdhe GdTQYjI GdQOjaI(B. s
Keywords: (3GdbQBfs -- (3JLhjOs -- (3OQGSI hJYdjes -- (3JMajX GdbQBfs -- (3JYdje GdbQBfs